2004
DOI: 10.1002/anie.200353313
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Natural Myriaporones

Abstract: Myriaporones 1-4 (1-4, respectively) are a new class of cytotoxic marine polyketide-derived compounds that exhibit significant cytotoxic activity against L1210 cells. These compounds 1-4 were isolated by Rinehart and co-workers in 1995 from the bryozoan Myriapora truncata.[1] The most active constituents, 3 and 4, were isolated as a mixture of cyclic and open-chain isomers. The myriaporones are structurally related to the C10-C23 region of the macrocycles tedanolide (5) [2] and deoxytedanolide (6), [3,4] alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…577,578 The total syntheses of myriaporones 1 648, 3 649 and 4 650 have been reported by two groups allowing determination of the previously undetermined C-5 and C-6 configurations. 579,580 The first enantioselective synthesis of the Flustra foliacea metabolite (-)-flustramine B 581 has been accomplished, employing a cascade addition-cyclisation strategy. 582…”
Section: Bryozoansmentioning
confidence: 99%
“…577,578 The total syntheses of myriaporones 1 648, 3 649 and 4 650 have been reported by two groups allowing determination of the previously undetermined C-5 and C-6 configurations. 579,580 The first enantioselective synthesis of the Flustra foliacea metabolite (-)-flustramine B 581 has been accomplished, employing a cascade addition-cyclisation strategy. 582…”
Section: Bryozoansmentioning
confidence: 99%
“…6 In subsequent synthetic studies of the myriaporones, equilibrium mixtures were also reported. 7,8 Therefore, structure determination of the two isomers was carried out on the mixture of 1 and 2 . HRESIMS data ( m/z 665.3146 [M + Na] + , Δ = 0.3 ppm) indicated that the molecular formula for both 1 and 2 , was C 32 H 50 O 13 ; two oxygens more than the molecular formula for tedanolide ( 5 ), and 42 Da less than the molecular weight of candidaspongiolide A ( 3 ).…”
mentioning
confidence: 99%
“…An important phase of this research has been completed. The efficiency of the synthetic route presented herein has enabled the preparation of significant quantities of these interesting marine natural products as well as analogues 12. Studies currently underway will seek to identify the biological receptor and mode of action of the myriaporones.…”
Section: Methodsmentioning
confidence: 99%